PEDAGOGICAL MONITORING OF ONLINE COURSES, A PRACTICE TO PROMOTE QUALITY IN THE UNED (Revista Electrónica Calidad en la Educación Superior, 2017)
Abstract The State Distance University (UNED) of Costa Rica is a higher education institution that currently makes intensive use of some technological means, in particular, online learning platforms. The implementation of this tool merits the creation of mechanisms that promote and raise the quality of online courses, paying attention to previously defined specific criteria. An important strategy to ensure compliance with these criteria is the monitoring or pedagogical supervision of the online courses, in which a review of the teachers' compliance with regard to the structure, mediation and attention of tending communication spaces is carried out. to provide the necessary feedback for continuous improvement. In this article, we present the results of a qualitative research, whose unit of analysis are all those tutors that have been part of the pedagogical monitoring process, as well as the executors of said activity; where, the information was collected through an online questionnaire. It seeks to analyze the relevance of monitoring for the instances of the university and the benefits it can bring to the improvement of online courses, as part of the experience developed in the UNED. Fortunately, in the totality of the responses received, this activity was considered of high value, by enabling continuous improvement, and offering a better learning process to the students, for which reason, it is contemplated that the practice of monitoring can be a reference for those institutions that use the virtual modality and wish to improve academic supervision in these environments, as well as the feedback that can be given to the teacher in his work.